FAKTOR-FAKTOR PENDORONG PERUBAHAN GUNA LAHAN KOTA-KOTA BESAR DI INDONESIA - Widayati, Noor; Marsoyo, Agam (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2026)
Indonesia has rapidly growing major cities, and this urban development significantly influences land use change. Analyzing land use changes in major cities can help to understand their characteristics and generate insights that are useful for future urban planning and policy formulation. This study aims to identify the driving factors of land use change in major cities in Indonesia. The research employs an inductive approach using qualitative content analysis, with data collected through a literature review. The data sources consist of documents discussing land use change across 26 major cities in Indonesia. The results show that the key driving factors of land use change include city location, industrial area development, road construction, the expansion and enhancement of transportation hubs, transportation system development, population growth, and the increase in trade and service activities. These driving factors are closely related to the direction of urban development. In industrial-oriented urban development, the expansion of industrial areas emerges as the primary driver, influencing other land use change factors.